Branch heterostructure piezoelectric fiber, piezoelectric nano generator and preparation method and application thereof
By using branch heterostructured piezoelectric fibers in flexible piezoelectric nanogenerators, the microstructure of piezoelectric fillers is optimized, and the problem of polarization voltage being consumed by polymer matrix is solved, the output performance is significantly improved, and through machine learning High accuracy monitoring of the power grid anti-vibration device is achieved.
Patent Information
- Application Number
- CN202411444768.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-16
AI Technical Summary
During the polarization process of existing flexible piezoelectric nanogenerators, most of the polarization voltages are consumed by polymer matrix, resulting in the low effective polarization voltage of the piezoelectric filler, which limits its output performance and sensing monitoring fields. Application.
Using the preparation method of branch and trunk heterostructure piezoelectric fibers, barium titanate-based nanospheres were prepared by hydrothermal method, and combined with coaxial electrospinning technology and chemical reduction method, Ag nanoparticles were deposited on barium titanate fibers to form Branch and trunk heterostructure, optimize the microstructure of piezoelectric filler to improve the effective polarization electric field.
Significantly improves the output performance of piezoelectric nanogenerators, with a maximum output voltage of 96.4V and an output current of 15.52 µA, enhancing the application capabilities in the field of sensing monitoring, and achieving high accuracy of the grid vibration-proof device through machine learning. rate monitoring.
Smart Images

Figure CN119287558A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic devices, and in particular to a branch-trunk heterogeneous structure piezoelectric fiber, a piezoelectric nanogenerator, and a preparation method and application thereof. Background Art
[0002] Flexible piezoelectric nanogenerators (PENGs) based on organic / inorganic composite films can obtain electrical energy from the surrounding environment and can be widely used in the Internet of Things (IoT) to capture clean energy to power low-power electronic devices to alleviate the energy crisis and reduce the maintenance cost of replacing batteries. At the same time, PENGs can also be used as active sensing units to capture electrical signals in the environment, which is very suitable for use in self-powered monitoring and sensing systems. Generally, in the prior art, such flexible PENGs are prepared by adding inorganic piezoelectric fillers to an organic polymer matrix in an appropriate proportion to form a composite film, and then polarizing the composite film and encapsulating it into a PENG. Inorganic piezoelectric fillers provide PENG with excellent piezoelectric properties, which directly affect the electrical output of PENG; while organic polymer materials have good flexibility, allowing PENG to meet the needs of different working conditions. However, after preparing PENG according to the existing traditional technology, the piezoelectric filler is wrapped in a polymer matrix with better insulation. This will result in that during the polarization process of the composite material, most of the polarization voltage will be consumed by the polymer material, and the effective polarization voltage actually acting on the piezoelectric filler is not high, which seriously affects the output of PENG and limits its application in the field of sensing and monitoring. For example, the patent application for a piezoelectric nanogenerator and its preparation method and a wireless sensor system previously proposed by our research group is CN117161378A. The solution a containing barium titanate / PVDF with silver nanospheres on the surface and the solution b containing barium titanate / PVDF are coaxially electrospun, wherein the solution a is the inner side of the coaxial and the solution b is the inner side of the coaxial, to obtain a coaxial heterostructure composite piezoelectric fiber. This synthesis method can prepare a PENG with higher performance by one-time film formation through electrospinning technology, and has the characteristics of simple synthesis process and excellent performance. However, in this process, the microstructure design of the piezoelectric filler is not performed to make the effective polarization electric field better. Therefore, it is of great significance to further optimize the design of the piezoelectric fiber microstructure to further improve the electrical output of PENG. Summary of the invention
[0003] In order to solve the above technical problems, the present invention proposes a branch-trunk heterostructure piezoelectric fiber, a piezoelectric nanogenerator, and a preparation method and application thereof.
[0004] To achieve the above object, the technical solution of the present invention is implemented as follows: A method for preparing a branch-trunk heterostructure piezoelectric fiber, the steps are as follows: (1) BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate were dissolved in water, NaOH was added to obtain a mixed solution, and barium titanate-based nanospheres (BCZT-SP) were prepared by a hydrothermal method; the obtained BCZT-SP was dissolved in a solvent to obtain solution 2; (2) Ba(OH)2·8H2O, Ca(OH)2, Zr(C5H8O2)4 and tetrabutyl titanate are dissolved in a mixed solvent of acetic acid and ethylene glycol methyl ether to obtain solution 1; (3) Solution 1 and solution 2 were subjected to coaxial electrospinning technology and then sintered to prepare BCZT-NF@BCZT-SP piezoelectric fibers; solution 1 was the coaxial electrospun inner layer structure solution, and solution 2 was the coaxial electrospun outer layer structure solution; (4) Ag nanoparticles were deposited on the BCZT-NF@BCZT-SP piezoelectric fibers prepared in step (2) using a chemical reduction method to prepare branch-stem heterostructure piezoelectric fibers.
[0005] In the above step (1), the molar ratio of BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate is (8-9):(1.2-1.6):(0.8-1.1):(9.5-10.5), and the Ba in the mixed solution is 2+ The concentration of Ba is 0.07-0.09 mol / L. 2+ With OH - The molar ratio is 1:(4-6); the reaction temperature of the hydrothermal method is 190-210°C and the time is 18-24 h.
[0006] In the solution 2 of the above step (1), the solvent is a mixed solvent of acetic acid, ethylene glycol methyl ether and acetylacetone (the volume ratio of the three is 6:6:1), and the molar concentration of BCZT-SP is 0.04-0.07 mol / L.
[0007] Furthermore, polyvinyl pyrrolidone is also added to the solution 2 in the above step (1) to adjust the viscosity of the solution.
[0008] In the above step (2), the molar ratio of Ba(OH)2·8H2O, Ca(OH)2, Zr(C5H8O2)4 and tetrabutyl titanate is (8-9):(1-2): (0.6-1.2): (9-10). 2+ The concentration is 0.33-0.38 mol / L.
[0009] The process parameters of the coaxial electrospinning technology in the above step (3) are: voltage 16-18 kV, roller speed 200-300 rpm, injection flow rate 15-20 μL / min; sintering temperature is 750-800°C, and time is 4-6 h.
[0010] The specific steps of the chemical reduction method in the above step (4) are: (S1) Adding BCZT-NF@BCZT-SP piezoelectric fibers to a mixed solution of SnCl2 and HCl I, stirring for 1-2 hours, filtering and washing the obtained particles, placing them in a silver ammonia solution, stirring for 0.5-1.5 hours, and obtaining BCZT-NF@BCZT-SP with Ag crystals on the surface; (S2) placing the BCZT-NF@BCZT-SP with Ag crystals on the surface in step (S1) in a mixed solution II consisting of formaldehyde solution, silver ammonia solution and alcohol, stirring the mixture for reaction, and obtaining a branch-trunk heterostructure piezoelectric fiber.
[0011] In the mixed solution I of the above step (S1), the concentration of SnCl2 is 0.06-0.08 mol / L, the concentration of HCl is 0.01-0.02 mol / L, and the concentration of silver ammonia solution is 0.25-0.45 mol / L.
[0012] The volume ratio of formaldehyde solution, silver ammonia solution and alcohol in the mixed solution II in the above step (S2) is (1-1.5): (4-8): (8-12), and the mass volume ratio of BCZT-NF@BCZT-SP covered with Ag crystals on the surface to the mixed solution II is 1g: (35-45) mL.
[0013] Furthermore, in the above step (S2), the concentration of the formaldehyde solution is 0.02-0.04 mol / L, the concentration of the silver ammonia solution is 0.25-0.45 mol / L, and the concentration of the alcohol is above 99.5%.
[0014] Furthermore, the stirring reaction time in the above step (S2) is at least 24 hours to facilitate sufficient reaction.
[0015] The branch-trunk heterogeneous structure piezoelectric fiber is prepared by the above preparation method.
[0016] The above-mentioned branch-trunk heterostructure piezoelectric fiber is used as a filler in a piezoelectric nanogenerator.
[0017] A method for preparing a piezoelectric nanogenerator based on branch-stem heterostructure piezoelectric fibers, the steps are as follows: (a) adding branch-stem heterostructure piezoelectric fibers and polyvinylidene fluoride into N,N-dimethylacetamide and stirring, and preparing the resulting mixed solution into a composite film on a coating machine by a casting method; (b) The composite film prepared in step (a) is encapsulated into a piezoelectric nanogenerator via electrodes and polyimide.
[0018] Furthermore, in the step (a), the mass ratio of the branch-trunk heterostructure piezoelectric fiber to polyvinylidene fluoride is 1:4; and the concentration of the heterostructure piezoelectric fiber in the mixed solution is 0.02-0.04 g / mL.
[0019] Furthermore, the stirring time in step (a) is 8-10 hours.
[0020] The piezoelectric nanogenerator (PENG) obtained by the above preparation method.
[0021] The above-mentioned piezoelectric nanogenerator is applied to a monitoring sensor system of a power grid vibration isolation device.
[0022] Furthermore, in the power grid vibration isolation device monitoring sensor system constructed based on the PENG of the present invention, the PENG is used as an active sensor to capture the vibration signal of the conductor and transmit it to the computer receiving end for identification and judgment. The system can judge the vibration isolation device according to the vibration state of the transmission line.
[0023] The beneficial effects produced by the present invention are: (1) The present invention provides a solution to the problem of low effective polarization electric field in flexible materials based on organic / inorganic composite membranes, thereby improving the output performance of PENG. The present invention designs a branch-stem heterostructure piezoelectric fiber filler, and combines the chemical sol-gel method and coaxial electrospinning technology to "graft" barium titanate-based nanospheres (BCZT-SP@Ag) coated with nano-Ag on the surface of barium titanate-based fibers (BCZT-NF) to make a branch-stem heterostructure piezoelectric fiber (BCZT-NF@BCZT-SP@Ag). In the present invention, the carrier activity in the interface region of organic / inorganic materials can be optimized by adjusting the structural ratio of the piezoelectric filler (BCZT-NF@BCZT-SP@Ag), thereby improving the effective polarization electric field, thereby further improving the output performance of PENG. Then, polyvinylidene fluoride (PVDF) was used as a flexible matrix to prepare a PENG based on the BCZT-NF@BCZT-SP@Ag / PVDF composite film. The PENG prepared using the technology of the present invention can provide a higher piezoelectric output (the maximum output voltage can be as high as 96.4V) and an output current of 15.52 µA. The enhanced output performance is more conducive to the practical application of PENG in the field of sensing and monitoring.
[0024] (2) The PENG prepared by the present invention is applied to the power grid to construct a wire vibration sensing monitoring system based on the PENG. The power grid vibration isolation device monitoring sensing system constructed by the PENG of the present invention uses the PENG as an active sensor to capture the vibration signal of the wire and transmit it to the computer receiving end for identification and judgment. The system can judge the vibration isolation device according to the vibration state of the transmission line. Then, the three results are learned and judged through machine learning. The specific process of machine learning: use a deep learning model to classify one-dimensional time series signals. Moreover, as the training process proceeds, the classification performance of the model gradually improves and tends to be stable. Finally, the system judgment accuracy based on the PENG of the present invention can reach more than 95%.
[0025] (3) The present invention effectively improves the electrical output performance of PENG and expands the application scenarios of PENG by designing the microstructure of piezoelectric fibers. The PENG in the present invention is combined with machine learning to design a system for abnormal monitoring of the anti-vibration device of power transmission lines in the power grid, which is conducive to the realization of self-powered smart grid sensors and the reduction of on-site maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The invention discloses a preparation process of a nanogenerator based on branch-stem heterostructure piezoelectric fibers.
[0028] Figure 2 SEM image of the branch-stem heterogeneous structure fiber (a); XRD pattern (b); TEM image (c) and SEM image of the cross section of the composite membrane (d).
[0029] Figure 3 (a) Polarization potential simulation, (b) generated piezoelectric potential simulation and (c) electrical output test of PENG based on three different piezoelectric fiber fillers.
[0030] Figure 4 The display images of the monitoring sensor system of the power grid vibration isolation device constructed based on the PENG of the present invention in normal operation (a) and abnormal state (b) of the vibration isolation device; (ce) feature data extraction based on PENG monitoring in three states; (f) training accuracy; (h) training error value; (i) chessboard diagram for judging the training results. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Raw materials: BaCl2·H2O (99.5%), ZrOCl2·8H2O (98%), CaCl2(96%) and tetrabutyl titanate were purchased from Aladdin Chemical Reagent Company; polyvinylidene fluoride (average molecular weight Mw~275,000), Ba(OH)2·8H2O (98%), Ca(OH)2(99%), Zr(C5H7O2)4(97%) were purchased from Sigma-Aldrich Chemical Reagent Company. AgNO3(99%) and SnCl2(98%) were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0033] Example 1 A preparation method of a branch-stem heterogeneous structure piezoelectric fiber of this embodiment, the preparation flow chart is as follows Figure 1 As shown, the steps are as follows: (1) BCZT-SP was prepared by hydrothermal method using BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate as raw materials. 1.91 g BaCl2·H2O, 0.16 g CaCl2, 0.31 g ZrOCl2·8H2O and 3.23 g tetrabutyl titanate were uniformly stirred in 100 mL distilled water and placed in a reactor. An appropriate amount of NaOH was added to the reactor to make BaCl2·H2O and CaCl2·ZrOCl2·8H2O reach the target concentration of 1.91 g. 2+ With OH - The ratio of 1:5. The mixed solution in the reactor was reacted at 200 °C for 24 h, and the obtained material was the synthesized BCZT-SP.
[0034] (2) Ba(OH)2·8H2O, Zr(C5H7O2)4, Ca(OH)2 and tetrabutyl titanate were used as raw materials for preparing BCZT-NF, and BCZT-NF@BCZT-SP piezoelectric fibers were prepared by coaxial electrospinning technology. 2.7 g Ba(OH)2·8H2O, 0.11 g Ca(OH)2, 0.49 g Zr(C5H8O2)4 and 3.06 g tetrabutyl titanate were mixed with 12 mL acetic acid and 12 mL ethylene glycol methyl ether to prepare solution 1; 0.4 g BCZT-SP (0.0018 mol) was mixed with 26 mL solvent (a mixed solvent of acetic acid, ethylene glycol methyl ether and acetylacetone in a volume ratio of 6:6:1) to prepare solution 2, and 3 g polyvinyl pyrrolidone was used to adjust the viscosity of the solution. The sol was prepared into low-humidity prefabricated fibers using coaxial electrospinning technology at a voltage of 18 kV, a spindle speed of 200 rpm, and an injection flow rate of 20 μL / min ( Figure 1 a). The low-humidity prefabricated fiber is placed in a muffle furnace and sintered to obtain BCZT-NF@BCZT-SP piezoelectric fiber ( Figure 1 b), sintering temperature is 750℃ and time is 4.5h.
[0035] (3) Ag nanoparticles were deposited on high surface energy BCZT-SP by chemical reduction method to prepare branch-stem heterostructure piezoelectric fibers (BCZT-NF@BCZT-SP@Ag). First, 0.3 g of BCZT-NF@BCZT-SP fibers were washed with deionized water and added into a mixed solution of 1.5 mL of SnCl2 and 1 mL of HCl, and stirred for 2 hours, where the concentration of SnCl2 was 0.07 mol / L and the concentration of HCl was 0.01 mol / L. Then, the obtained particles were filtered and washed with deionized water and placed in 40 mL of silver ammonia solution with a concentration of 0.3 mol / L and stirred for 1 h to allow the Ag nanocrystals to be coated on the surface of BCZT-NF@BCZT-SP. Finally, 0.3 g of BCZT-NF@BCZT-SP fiber with Ag crystals on the surface was placed in a mixed solution consisting of 1 mL of formaldehyde solution, 4 mL of silver ammonia solution and 8 mL of alcohol and stirred for at least 24 hours for sufficient reaction, thereby obtaining branch-stem heterostructure piezoelectric fiber (BCZT-NF@BCZT-SP@Ag) ( Figure 1 c), wherein the concentration of the formaldehyde solution is 0.02 mol / L, the concentration of the silver ammonia solution is 0.3 mol / L, and the concentration of the alcohol is above 99.5%.
[0036] Figure 2a is a scanning electron microscope (SEM) microscopic image of the branch-stem heterostructure BCZT-NF@BCZT-SP@Ag fiber. The fiber diameter is 200-400 nm, and the heterostructured BCZT-SP@Ag particles have been successfully "grafted" onto the BCZT fiber. Figure 2 b is the X-ray diffraction test pattern (XRD) of the branch-stem heterogeneous structure fiber, in which the diffraction peaks at approximately 21.9°, 31.7°, 38.1°, 45.2°, 55.7° and 65.4° correspond to the (100), (110), (111), (200), (211) and (220) crystal planes of BCZT, respectively; and the diffraction peaks at 38.5°, 44.2°, 64.2° and 77.5° correspond to the (111), (200), (220) and (311) crystal planes of face-centered cubic structure Ag, respectively. Figure 2 c is a TEM photo of a single branch-structured fiber, the diameter of the fiber is about 200 nm; from the local magnified image, it can be seen that small Ag nanoparticles are attached to the surface of BCZT-SP, forming a heterogeneous structure.
[0037] A method for preparing a nanogenerator based on branch-stem heterostructure piezoelectric fibers, the preparation flow chart of which is as follows: Figure 1 As shown, the steps are as follows: 0.75 g BCZT-NF@BCZT-SP@Ag prepared in this example and 3 g polyvinylidene fluoride were stirred in 30 mL N,N-dimethylacetamide for 8 h ( Figure 1 d). The obtained mixed solution is prepared into a composite film on a coating machine by a casting method ( Figure 1 e), and then encapsulated by electrodes and polyimide to form PENG ( Figure 1 f).
[0038] Figure 2 d is the cross-sectional SEM image of the composite membrane made by incorporating BCZT-NF@BCZT-SP@Ag fibers into the PVDF matrix. It can be seen from the figure that the BCZT-NF@BCZT-SP@Ag fibers (in the red circle) are relatively evenly distributed in PVDF without obvious agglomeration.
[0039] Figure 3a and 3b are simulations of the polarization potential and piezoelectric potential of three PENGs based on different piezoelectric fibers (traditional BCZT-NF fiber, improved BCZT-NF@BCZT-SP fiber and branch-heterogeneous structure BCZT-NF@BCZT-SP@Ag fiber) under the same polarization conditions using COMOSL multi-physics simulation software. The results show that the present invention can significantly improve the polarization voltage distribution acting on the fiber filler, increase the polarization potential difference, and fully polarize the piezoelectric filler, from 2.6 kV to 7.2 kV ( Figure 3 a); then, under the action of 30N external force, Figure 3 b shows the piezoelectric potential generated by PENG on the surface. The results show that the designed branch-stem heterostructure fiber will generate a larger piezoelectric potential, which increases from 22 V to 48 V. Figure 3 c is the electrical output test of PENG based on the above three piezoelectric fibers. The results show that compared with traditional fiber fillers, the fiber fillers designed based on the present invention can improve the output performance of PENG by more than 3 times, among which the output voltage is increased from 30.6 V to 96.4 V, and the output current is increased from 2.40 µA to 15.52 µA. The enhanced output performance is more conducive to the practical application of PENG in the field of sensing and monitoring.
[0040] Example 2 A preparation method of a branch-stem heterogeneous structure piezoelectric fiber of this embodiment, the preparation flow chart is as follows Figure 1 As shown, the steps are as follows: (1) BCZT-SP was prepared by hydrothermal method using BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate as raw materials. 2.04 g BaCl2·H2O, 0.13 g CaCl2, 0.26 g ZrOCl2·8H2O and 3.57 g tetrabutyl titanate were uniformly stirred in 100 mL distilled water and placed in a reactor. An appropriate amount of NaOH was added to the reactor to make BaCl2·H2O and CaCl2·ZrOCl2·8H2O reach 100 mL distilled water. 2+ With OH - The ratio of 1:4. The mixed solution in the reactor was reacted at 210°C for 18 h, and the obtained material was the synthesized BCZT-SP.
[0041] (2) Ba(OH)2·8H2O, Zr(C5H7O2)4, Ca(OH)2 and tetrabutyl titanate were used as raw materials for preparing BCZT-NF, and BCZT-NF@BCZT-SP piezoelectric fibers were prepared by coaxial electrospinning technology. 2.52 g Ba(OH)2·8H2O, 0.074 g Ca(OH)2, 0.478 g Zr(C5H8O2)4 and 3.06 g tetrabutyl titanate were mixed with 12 mL acetic acid and 12 mL ethylene glycol methyl ether to prepare solution 1; 0.22 g BCZT-SP (0.001 mol) was mixed with 26 mL solvent (a mixed solvent of acetic acid, ethylene glycol methyl ether and acetylacetone in a volume ratio of 6:6:1) to prepare solution 2, and 3 g polyvinyl pyrrolidone was used to adjust the viscosity of the solution. The sol was prepared into low-humidity prefabricated fibers by coaxial electrospinning technology, with a voltage of 16 kV, a roller speed of 300 rpm, and an injection flow rate of 15 μL / min. The low-humidity prefabricated fibers were sintered in a muffle furnace to obtain BCZT-NF@BCZT-SP piezoelectric fibers, with a sintering temperature of 800°C and a sintering time of 4 h.
[0042] (3) Ag nanoparticles were deposited on high surface energy BCZT-SP by chemical reduction method to prepare branch-stem heterostructure piezoelectric fibers (BCZT-NF@BCZT-SP@Ag). First, 0.3 g of BCZT-NF@BCZT-SP fibers were washed with deionized water and added into a mixed solution of 1.5 mL of SnCl2 and 1 mL of HCl, and stirred for 2 hours, where the concentration of SnCl2 was 0.06 mol / L and the concentration of HCl was 0.02 mol / L. Subsequently, the obtained particles were filtered and washed with deionized water and placed in 40 mL of silver ammonia solution with a concentration of 0.25 mol / L and stirred for 1 h to allow the Ag nanocrystals to be coated on the surface of BCZT-NF@BCZT-SP; finally, 0.38 g of BCZT-NF@BCZT-SP fiber with Ag crystals on the surface was placed in a mixed solution consisting of 1 mL of formaldehyde solution, 4 mL of silver ammonia solution and 12 mL of alcohol and stirred for at least 24 hours for sufficient reaction to obtain branch-stem heterostructure piezoelectric fiber (BCZT-NF@BCZT-SP@Ag), wherein the concentration of the formaldehyde solution was 0.03 mol / L, the concentration of the silver ammonia solution was 0.25 mol / L, and the concentration of the alcohol was above 99.5%.
[0043] A method for preparing a nanogenerator based on branch-stem heterostructure piezoelectric fibers, the preparation flow chart of which is as follows: Figure 1 As shown, the steps are as follows: 0.6 g BCZT-NF@BCZT-SP@Ag prepared in this example and 2.4 g polyvinylidene fluoride were fully stirred in 30 mL N,N-dimethylacetamide for 10 h. The resulting mixture was cast into a composite film on a coating machine, and then encapsulated into a PENG by electrodes and polyimide.
[0044] Example 3 A preparation method of a branch-stem heterogeneous structure piezoelectric fiber of this embodiment, the preparation flow chart is as follows Figure 1 As shown, the steps are as follows: (1) BCZT-SP was prepared by hydrothermal method using BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate as raw materials. 1.81 g BaCl2·H2O, 0.18 g CaCl2, 0.35 g ZrOCl2·8H2O and 3.40 g tetrabutyl titanate were uniformly stirred in 114 mL distilled water and placed in a reactor. An appropriate amount of NaOH was added to the reactor to make BaCl2·H2O and CaCl2·ZrOCl2·8H2O. 2+ With OH - The ratio of 1:6. The mixed solution in the reactor was reacted at 190°C for 24 h, and the obtained material was the synthesized BCZT-SP.
[0045] (2) Ba(OH)2·8H2O, Zr(C5H7O2)4, Ca(OH)2 and tetrabutyl titanate were used as raw materials for preparing BCZT-NF, and BCZT-NF@BCZT-SP piezoelectric fibers were prepared by coaxial electrospinning technology. 2.84 g Ba(OH)2·8H2O, 0.15 g Ca(OH)2, 0.29 g Zr(C5H8O2)4 and 3.40 g tetrabutyl titanate were mixed with 12 mL acetic acid and 12 mL ethylene glycol methyl ether to prepare solution 1; 0.3 g BCZT-SP (0.0013 mol) was mixed with 26 mL solvent (a mixed solvent of acetic acid, ethylene glycol methyl ether and acetylacetone in a volume ratio of 6:6:1) to prepare solution 2, and 3 g polyvinyl pyrrolidone was used to adjust the viscosity of the solution. The sol was prepared into low-humidity prefabricated fibers by coaxial electrospinning technology, with a voltage of 17 kV, a roller speed of 250 rpm, and an injection flow rate of 17 μL / min. The low-humidity prefabricated fibers were sintered in a muffle furnace to obtain BCZT-NF@BCZT-SP piezoelectric fibers, with a sintering temperature of 750°C and a sintering time of 6 h.
[0046] (3) Ag nanoparticles were deposited on high surface energy BCZT-SP by chemical reduction method to prepare branch-stem heterostructure piezoelectric fibers (BCZT-NF@BCZT-SP@Ag). First, 0.3 g of BCZT-NF@BCZT-SP fibers were washed with deionized water and added into a mixed solution of 1.5 mL of SnCl2 and 1 mL of HCl, and stirred for 2 hours, where the concentration of SnCl2 was 0.08 mol / L and the concentration of HCl was 0.015 mol / L. Then, the obtained particles were filtered and washed with deionized water and placed in 40 mL of silver ammonia solution with a concentration of 0.45 mol / L and stirred for 1 h to allow the Ag nanocrystals to be coated on the surface of BCZT-NF@BCZT-SP; finally, 0.48 g of BCZT-NF@BCZT-SP fiber with Ag crystals on the surface was placed in a mixed solution consisting of 1 mL of formaldehyde solution, 8 mL of silver ammonia solution and 8 mL of alcohol and stirred for at least 24 hours for sufficient reaction to obtain branch-stem heterostructure piezoelectric fiber (BCZT-NF@BCZT-SP@Ag), wherein the concentration of the formaldehyde solution was 0.04 mol / L, the concentration of the silver ammonia solution was 0.45 mol / L, and the concentration of the alcohol was above 99.5%.
[0047] A method for preparing a nanogenerator based on branch-stem heterostructure piezoelectric fibers, the preparation flow chart of which is as follows: Figure 1 As shown, the steps are as follows: 1.2 g BCZT-NF@BCZT-SP@Ag prepared in this example and 4.8 g polyvinylidene fluoride were fully stirred in 30 mL N,N-dimethylacetamide for 8 h. The resulting mixture was cast into a composite film on a coating machine, and then encapsulated into a PENG with electrodes and polyimide.
[0048] Example 4 A preparation method of a branch-stem heterogeneous structure piezoelectric fiber of this embodiment, the preparation flow chart is as follows Figure 1 As shown, the steps are as follows: (1) BCZT-SP was prepared by hydrothermal method using BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate as raw materials. 1.91 g BaCl2·H2O, 0.16 g CaCl2, 0.31 g ZrOCl2·8H2O and 3.23 g tetrabutyl titanate were uniformly stirred in 100 mL distilled water and placed in a reactor. An appropriate amount of NaOH was added to the reactor to make BaCl2·H2O and CaCl2·ZrOCl2·8H2O reach the target concentration of 1.91 g. 2+ With OH - The ratio of 1:5. The mixed solution in the reactor was reacted at 200°C for 21 h, and the obtained material was the synthesized BCZT-SP.
[0049] (2) Ba(OH)2·8H2O, Zr(C5H7O2)4, Ca(OH)2 and tetrabutyl titanate were used as raw materials for preparing BCZT-NF, and BCZT-NF@BCZT-SP piezoelectric fibers were prepared by coaxial electrospinning technology. 2.6 g Ba(OH)2·8H2O, 0.13 g Ca(OH)2, 0.38 g Zr(C5H8O2)4 and 3.2 g tetrabutyl titanate were mixed with 12 mL acetic acid and 12 mL ethylene glycol methyl ether to prepare solution 1; 0.35 g BCZT-SP (0.0016 mol) was mixed with 26 mL solvent (a mixed solvent of acetic acid, ethylene glycol methyl ether and acetylacetone in a volume ratio of 6:6:1) to prepare solution 2, and 3 g polyvinyl pyrrolidone was used to adjust the viscosity of the solution. The sol was prepared into low-humidity prefabricated fibers by coaxial electrospinning technology, with a voltage of 18 kV, a roller speed of 200 rpm, and an injection flow rate of 20 μL / min. The low-humidity prefabricated fibers were sintered in a muffle furnace to obtain BCZT-NF@BCZT-SP piezoelectric fibers, with a sintering temperature of 780°C and a sintering time of 5 h.
[0050] (3) Ag nanoparticles were deposited on high surface energy BCZT-SP by chemical reduction method to prepare branch-stem heterostructure piezoelectric fibers (BCZT-NF@BCZT-SP@Ag). First, 0.3 g of BCZT-NF@BCZT-SP fibers were washed with deionized water and added into a mixed solution of 1.5 mL of SnCl2 and 1 mL of HCl, and stirred for 2 hours, where the concentration of SnCl2 was 0.07 mol / L and the concentration of HCl was 0.01 mol / L. Subsequently, the obtained particles were filtered and washed with deionized water and placed in 40 mL of silver ammonia solution with a concentration of 0.3 mol / L and stirred for 1 h to allow the Ag nanocrystals to be coated on the surface of BCZT-NF@BCZT-SP; finally, 0.54 g of BCZT-NF@BCZT-SP fiber with Ag crystals on the surface was placed in a mixed solution consisting of 1.5 mL of formaldehyde solution, 8 mL of silver ammonia solution and 12 mL of alcohol and stirred for at least 24 hours for sufficient reaction to obtain branch-stem heterostructure piezoelectric fiber (BCZT-NF@BCZT-SP@Ag), wherein the concentration of formaldehyde solution was 0.02 mol / L, the concentration of silver ammonia solution was 0.3 mol / L, and the concentration of alcohol was above 99.5%.
[0051] A method for preparing a nanogenerator based on branch-stem heterostructure piezoelectric fibers, the preparation flow chart of which is as follows: Figure 1 As shown, the steps are as follows: 0.6 g BCZT-NF@BCZT-SP@Ag prepared in this example and 2.4 g polyvinylidene fluoride were fully stirred in 20 mL N,N-dimethylacetamide for 8 h. The resulting mixture was cast into a composite film on a coating machine, and then encapsulated into PENG by electrodes and polyimide.
[0052] Application Examples Application of the PENG prepared by the present invention in a monitoring sensor system of a power grid vibration isolation device. Figure 4 Figures 4a and 4b are monitoring and sensing systems for power grid vibration isolation devices based on the PENG of the present invention. The PENG is used as an active sensor to capture the vibration signal of the conductor and transmit it to the computer receiving end for identification and judgment. The system can judge the vibration isolation device according to the vibration state of the transmission line, for example Figure 4 a shows the normal state, Figure 4 b shows an abnormal state (failure of the anti-vibration device). Figure 4 ce is the electrical signal of three different working states captured by PENG, which are normal operation of the anti-vibration device, looseness of the anti-vibration device, and failure of the anti-vibration device. Then, the three results are learned and judged by machine learning. Specific process of machine learning: Use deep learning model to classify one-dimensional time series signals. The data comes from three different categories of CSV files. First, preprocessing is performed by reading CSV files and converting data into floating point format. Then, StandardScaler is used to standardize the data to ensure that each feature has the same scale. After data processing, the data is divided into training set and test set, of which 20% of the data is used for testing and 80% of the data is used for training. A simple fully connected neural network (SimpleModel) is constructed using the PyTorch library, which includes an input layer, a hidden layer (100 neurons), and an output layer (for three-classification tasks). The training process adopts the cross entropy loss function (nn.CrossEntropyLoss) and the Adam optimizer (optim.Adam), with a learning rate of 0.02. The model was trained for 100 cycles, with a training data batch size of 64 in each cycle. At the end of each training cycle, the training loss and classification accuracy were recorded. To evaluate the model performance, the test set was used for prediction and the confusion matrix was calculated. To more intuitively display the classification results, a normalized confusion matrix was plotted, showing the classification accuracy of the model for each category. In addition, a loss change graph and classification accuracy curve during the training process were plotted to further verify the training effect of the model ( Figure 4f and 4h). Experimental results: Through the above experimental steps, we have achieved an effective time series signal classification method. The normalized confusion matrix shows the classification performance of the model between various categories. The classification accuracy and loss curves show that as the training process progresses, the classification performance of the model gradually improves and tends to be stable. Figure 4 i shows that the final system judgment accuracy based on the PENG of the present invention can reach more than 95%.
[0053] The present invention effectively improves the electrical output performance of PENG and expands the application scenarios of PENG through the microstructure design of piezoelectric fibers; the PENG in the present invention is combined with machine learning to design a system for abnormal monitoring of the anti-vibration device of power transmission lines in the power grid, which is conducive to the realization of self-powered power grid intelligent sensors and reduces the on-site maintenance costs of personnel.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a branch-trunk heterostructure piezoelectric fiber, characterized in that: Here are the steps: (1) BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate are dissolved in water, NaOH is added to obtain a mixed solution, and BCZT-SP is prepared by a hydrothermal method; the obtained BCZT-SP is dissolved in a solvent to obtain solution 2; (2) Ba(OH)2·8H2O, Ca(OH)2, Zr(C5H8O2)4 and tetrabutyl titanate are dissolved in a mixed solvent of acetic acid and ethylene glycol methyl ether to obtain solution 1; (3) Solution 1 and solution 2 were coaxially electrospun and then sintered to prepare BCZT-NF@BCZT-SP piezoelectric fibers; Wherein solution 1 is the coaxial electrospun inner layer structure solution, and solution 2 is the coaxial electrospun outer layer structure solution; (4) Ag nanoparticles were deposited on the BCZT-NF@BCZT-SP piezoelectric fibers prepared in step (2) using a chemical reduction method to prepare branch-stem heterostructure piezoelectric fibers.
2. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of BaCl2·H2O, CaCl2, ZrOCl2·8H2O and tetrabutyl titanate is (8-9):(1.2-1.6):(0.8-1.1):(9.5-10.5); Ba in the mixed solution 2+ The concentration of Ba is 0.07-0.09 mol / L. 2+ With OH - The molar ratio is 1:(4-6); the reaction temperature of the hydrothermal method is 190-210°C, and the time is 18-24 h; in solution 2, the solvent is a mixed solvent of acetic acid, ethylene glycol methyl ether and acetylacetone, and the molar concentration of BCZT-SP is 0.04-0.07 mol / L.
3. The preparation method according to claim 2, characterized in that: In step (2), the molar ratio of Ba(OH)2·8H2O, Ca(OH)2, Zr(C5H8O2)4 and tetrabutyl titanate is (8-9):(1-2): (0.6-1.2): (9-10). 2+ The concentration is 0.33-0.38 mol / L; the process parameters of the coaxial electrospinning technology in step (3) are: voltage 16-18 kV, roller speed 200-300 rpm, injection flow rate 15-20 μL / min; the sintering temperature is 750-800℃, and the time is 4-6 h.
4. The preparation method according to claim 3, characterized in that: The specific steps of the chemical reduction method in step (4) are: (S1) adding BCZT-NF@BCZT-SP piezoelectric fibers into a mixed solution of SnCl2 and HCl I, and placing the obtained particles into a silver ammonia solution after stirring, filtering and washing, to obtain BCZT-NF@BCZT-SP with Ag crystals on the surface; (S2) placing the BCZT-NF@BCZT-SP with Ag crystals on the surface in step (S1) in a mixed solution II consisting of formaldehyde solution, silver ammonia solution and alcohol, stirring the mixture for reaction, and obtaining a branch-trunk heterostructure piezoelectric fiber.
5. The preparation method according to claim 4, characterized in that: In the mixed solution I of step (S1), the concentration of SnCl2 is 0.06-0.08 mol / L, the concentration of HCl is 0.01-0.02 mol / L; the concentration of the silver ammonia solution is 0.25-0.45 mol / L; in the mixed solution II of step (S2), the concentration of the formaldehyde solution is 0.02-0.04 mol / L, the concentration of the silver ammonia solution is 0.25-0.45 mol / L, the concentration of the alcohol is above 99.5%, and the volume ratio of the formaldehyde solution, the silver ammonia solution and the alcohol is (1-1.5): (4-8): (8-12); the mass volume ratio of the BCZT-NF@BCZT-SP covered with Ag crystals on the surface to the mixed solution II is 1 g: (35-45) mL.
6. A branch-trunk heterogeneous structure piezoelectric fiber prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the branch-trunk heterostructure piezoelectric fiber according to claim 6 as filler in a piezoelectric nanogenerator.
8. A method for preparing a piezoelectric nanogenerator based on branch-stem heterostructure piezoelectric fibers, characterized in that: Here are the steps: (a) adding branch-stem heterostructure piezoelectric fibers and polyvinylidene fluoride into N,N-dimethylacetamide and stirring, and preparing the resulting mixed solution into a composite film by a casting method; (b) The composite film prepared in step (a) is encapsulated into a piezoelectric nanogenerator via electrodes and polyimide.
9. The piezoelectric nanogenerator obtained by the preparation method according to claim 8.
10. The piezoelectric nanogenerator according to claim 9 is applied to a monitoring sensor system of a power grid vibration isolation device.
Citation Information
Patent Citations
BCZT (Barium Calcium Zirconate Titanate)-based flexible piezoelectric composite fibre film, preparation method thereof and flexible piezoelectric nano-generator containing film
CN109667067A
Porous PVDF (Polyvinylidene Fluoride) composite material as well as nano generator and piezoelectric catalysis application thereof
CN116218105A
Piezoelectric nano generator, preparation method thereof and wireless sensing system
CN117161378A
Preparation method and catalytic sterilization application of DA-Ag-BCZT / PVDF flexible piezoelectric composite fiber film
CN118407192A
Piezoelectric-effect-induced heterogeneous electrochemical reactions
US20160214902A1